A Formação do professor: um estudo a partir da concepção de ética em Paul Ricoeur - Smarjassi, Célia Marilda [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The teaching practice claims, by essence and vocation, an eminently ethical action, because the teacher gives human form to the values, hence the importance of ethical formation of the teacher, for from this professional is expected a singular posture of being in the world. In this research we are looking to answer the following question: What are the principles and guidelines of the ethical thought of Paul Ricoeur that would provide an adequate analysis of the disposal of the National Curriculum Guidelines for the Graduation Course in Pedagogy, graduation and the National Curriculum Guidelines for the Training of Teachers of Basic Education, in higher education, degree course, full degree around ethics in teacher training? Methodologically this research appears as bibliographic and documentary, therefore theoretical. In conclusion we note that the official guidelines for the training of teacher bring misconception about the ethics conception. We notice that Ricoeur’s standing, about ethical living guides to a life marked by a behavior in which the person is guided by a self-criticism and self-analysis, and is able to assume attitudes consciously and responsibly, therefore we conclude that his thoughts about ethics might be a valuable tool to develop the teacher’s formation

A prática docente reclama por essência e vocação uma atuação eminentemente ética, porque ele, o professor, dá a forma humana aos valores, daí a importância da formação ética do professor, porque desse profissional se espera uma postura singular de ser e estar no mundo. Nesta pesquisa buscamos responder à seguinte questão: Quais são os princípios e as orientações do pensamento ético de Paul Ricoeur que propiciariam uma análise adequada do que dispõem as Diretrizes Curriculares Nacionais para o. Curso de Graduação em Pedagogia, licenciatura e das Diretrizes Curriculares Nacionais para a Formação de Professores da Educação Básica, em nível superior, curso de licenciatura, de graduação plena em torno da ética na formação de professores? Metodologicamente esta pesquisa configura-se como bibliográfica e documental, portanto teórica. Em conclusão observamos que as diretrizes oficiais para a formação do professor trazem equívocos quanto ao conceito de ética. Percebemos que as inferências de Ricoeur, acerca do viver ético apontam para um viver pautado por uma conduta em que o sujeito seja guiado por uma autocrítica e autoanálise, e que seja capaz de assumir atitudes de modo consciente e responsável, portanto concluímos que seu pensamento sobre ética pode ser uma valiosa ferramenta para se pensar a formação do professor
The preparation of a teacher: a study from the ethich conception of Paul Recoeur
Keywords: Ricoeur, Paul 1913-2005 Crítica e interpretação; Ética; Professores - Formação; Professores - Participação no planejamento curricular; Educação; Ethics